2003
DOI: 10.1212/01.wnl.0000049930.93113.20
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of 5-HT 1A receptor binding in patients with temporal lobe epilepsy

Abstract: These findings support the hypothesis of reduced serotonin receptor binding in temporal lobe epileptic foci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
1
7

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(120 citation statements)
references
References 47 publications
3
109
1
7
Order By: Relevance
“…In 12 patients with TLE, an initial PET study found lower [ 18 F]FCWAY V ipsilateral than contralateral to the epileptic focus in inferior medial and laterial temporal regions of patients; [ 18 F]FCWAY V was 29% lower in raphe and 34% lower in ipsilateral thalamic regions in TLE patients relative to healthy controls (52). The [ 18 F]FCWAY V mean asymmetry index was significantly greater than mean cerebral blood flow and mean glucose metabolism asymmetry index suggesting relatively specific reduction in 5-HT 1A receptor BP in temporal lobe epileptic focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 12 patients with TLE, an initial PET study found lower [ 18 F]FCWAY V ipsilateral than contralateral to the epileptic focus in inferior medial and laterial temporal regions of patients; [ 18 F]FCWAY V was 29% lower in raphe and 34% lower in ipsilateral thalamic regions in TLE patients relative to healthy controls (52). The [ 18 F]FCWAY V mean asymmetry index was significantly greater than mean cerebral blood flow and mean glucose metabolism asymmetry index suggesting relatively specific reduction in 5-HT 1A receptor BP in temporal lobe epileptic focus.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonininduced anticonvulsive effects were mediated specifically by hippocampal 5-HT 1A receptors (32). Patients with TLE have reduced 5-HT 1A receptor binding (52). The reductions in serotonin receptor binding were not limited to disease-specific brain regions, or explained by brain atrophy (19).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased 5-HT 1A receptor binding potential has been consistently found in multiple brain areas of patients with MDD (Drevets et al, 1999. This abnormality is not highly specific for MDD and has been found in patients with panic disorder and temporal lobe epilepsy (Toczek et al, 2003), and may explain the considerable comorbidity among these conditions. The lack of effect of selective serotonin reuptake inhibitor treatment and hydrocortisone challenge on 5-HT 1A receptors in recovered patients with MDD suggests state-independence of this abnormality (Bhagwagar et al, , 2004.…”
Section: Functional Imagingmentioning
confidence: 96%
“…6,7 The AEDs with established psychotropic effects (for example, carbamazepine, valproate, and lamotrigine) have been found to cause an increase in 5 hydroxytryptamine (5HT). 8 -10 The anticonvulsant protection of carbamazepine can be blocked with 5HT-depleting drugs in rats genetically prone to have seizures.…”
Section: Psychiatric Disordersmentioning
confidence: 99%